Designing the entrepreneurial government model in attracting and selecting public sector human resources - Atieh sarayani; Vahid Pourshahabi; Nourmohammad yaghobi; Amin reza kamaliyan (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to design an entrepreneurial government model in attracting and recruiting public sector human resources (case study: Sistan and Baluchistan province). The present research is applicable in terms of purpose; and exploratory in terms of nature; and it is specifically based on structural equation modeling. The statistical population of the research is all human resource managers and experts in government organizations located in Sistan and Baluchistan province, whose number in 2020 is about 700 people, and the sample size is based on the rule proposed by Bentler and Chu (1987), based on which a total of 390 people were selected by simple random sampling. The collection tool in this research is a researcher-made questionnaire, taken from the qualitative part. In order to analyze the data, structural equation technique was used using Lisrel statistical software and Spss statistical software. The results showed that for seven hypotheses out of the total of nine formulated hypotheses based on the research model, no evidence of rejection at the 5% error level has been obtained, and it has a positive and significant effect, and also the results of the average common values ​​and the average values ​​of R Squares show that the value of GOF is equal to 0.790, which indicates the strong fit of the model. Extended Abstract Introduction Human resources is the most valuable and important asset of an organization, and the individual and collective efforts of people are the result of the knowledge of thinking, creativity, and efficiency of human resource management that brings the organization closer or further away from the determined goals, and human resources management can play a key and vital role in the development of abilities and capabilities of the companies (Leroy et al, 2018); because it is almost impossible to achieve the goals of the organization without considering its human resources (Deljo et al, 2021). Therefore, the importance of human force management as the most prominent factor of competitive advantage in human resources management is effective directly in the efficiency and effectiveness of human resources (Soleimani Babadi et al, 2022). Today, entrepreneurship in the public sector has been able to improve productivity at various individual and organizational levels, which, of course, requires proper foundation. Therefore, currently, success belongs to organizations that establish a meaningful relationship between the managerial and entrepreneurial capabilities of their human and organizational resources (Kia Kojori & Ja'farian, 2012). In recent years, the strategic and potential impact of the process of recruiting and providing people has been increasingly noticed; because human capital as the main source of sustainable competitive advantage is being replaced by other forms of capital (Teimouri et al, 2018). Recruiting and finding the right people for the job is perhaps the most important topic that has been widely studied in the literature related to large and small organizations. The lack of qualified employees is not only a threat to the plans and development of the organization, but also the most important threat to the survival of an organization (Ahmadi et al, 2018). Therefore, how to select human resources in the organization is of particular importance (Farhi Bozanjani et al, 2012), and recruiting competent human resources that can perform properly towards the strategic goals of the organization is one of the most important duties of managers (Khaefelahi et al, 2014). Therefore, according to the importance and position of the subject, the main question that can be raised in this research is; What is the model of the entrepreneurial government in recruiting and selecting public sector human resources with a qualitative approach (case study: Sistan and Baluchistan Province)? Theoretical Framework Recruitment and selection of human resources The success or failure of the organization depends on how to attract and maintain its human resources. Also, choosing and employing the most qualified people in each job is considered one of the most important management issues and decisions. Recruiting and finding the right people for the job is perhaps the most important topic that has been widely studied in the literature related to large and small organizations. Although most small organizations do not have formal human resources departments, they all have recruitment and human resource policies. The lack of qualified employees is not only a threat to the plans and development of the organization, but it can also be the best threat to the survival of an organization (Ahmadi et al, 2018). Entrepreneurial government An entrepreneurial government organization means a major change in theory and practice, which by creating change and transformation in the government sector, improves the efficiency and effectiveness of government organizations. In other words, an entrepreneurial government is like a person who plans, gives, and implements new ideas in the government (Mili & Nasrullah, 2014). On the other hand, the entrepreneurial government is evaluated by change, innovation and reaching beneficial conditions and delivery of government services that complement the capital of society (Rajbar et al, 2019). A government entrepreneur is a person who undertakes the targeted activities of one or more government departments (Rajbar et al, 2019). Abidi et al, (2024) examined the purpose of the current research to identify and evaluate the components of human resource competence in the era of digital transformation. The results in the qualitative section showed that the competency of digital managers includes 7 components of individual factors, organizational factors, culture of change, digital attitude, communication factors, leadership and management, and technical and specialized factors. The results in the quantitative section showed that there is a significant correlation between all components. Also, among the components, the culture and change management component was given first priority. The results also showed that the research model has the required validity. Sarayani et al, (2024) examined the presentation of the model of recruitment and selection of public sector human resources with the entrepreneurial government approach. According to data analysis, 545 final codes were extracted through open coding and then, categorized using axial coding in the form of 121 concepts and 16 categories (contextual (environmental) factors, structural (organizational) factors, behavioral (content) factors, recruiting human resources, selecting human resources, identifying entrepreneurial opportunities in the public sector, exploiting entrepreneurial opportunities in the public sector, executive and managerial obstacles, political and legal obstacles, economic obstacles, cultural and social obstacles, combined selection with domination domestic resources in experience-based jobs, combined selection with external resources in knowledge-based jobs, individual consequences, organizational consequences, social consequences); and finally, in the selective coding stage, a process and multidimensional model is presented for the first time in the level of government organizations of Sistan and Baluchistan province. Research methodology The present research is applicable in terms of purpose; and exploratory in terms of nature; and it is specifically based on structural equation modeling. The statistical population of the research is all human resource managers and experts in government organizations located in Sistan and Baluchistan province, whose number in 2020 is about 700 people, and the sample size is based on the rule proposed by Bentler and Chu (1987), based on which a total of 390 people were selected by simple random sampling. The collection tool in this research is a researcher-made questionnaire, taken from the qualitative part. Research findings In order to analyze the data, structural equation technique was used using Lisrel statistical software and Spss statistical software. The results showed that for seven hypotheses out of the total of nine formulated hypotheses based on the research model, no evidence of rejection at the 5% error level has been obtained, and it has a positive and significant effect, and also the results of the average common values ​​and the average values ​​of R Squares show that the value of GOF is equal to 0.790, which indicates the strong fit of the model. Conclusion The current research was conducted with the aim of designing an entrepreneurial government model in attracting and recruiting public sector human resources (case study: Sistan and Baluchistan province). The results of this research are aligned with the results of Abidi et al, (2024), Sarayani et al, (2024), Gheiravani et al, (2023), Fazlali & Moazzami (2022), Munaty et al, (2022), Orakwue & Iguisi (2020), Moustaghfir et al, (2020), Hasanzade et al, (2020), Jalili et al, (2020), Noroozian et al, (2020), and Akhavan Kharazian et al, (2019). Hasanzade et al, (2020) showed that all recruitment processes in government organizations should have scientific and legal processes, so that in addition to reducing administrative corruption, employment justice is also established in the government departments of the province. According to the obtained results, the following suggestions are provided: 1- All recruitment processes in government organizations should have scientific and legal processes, so that in addition to reducing administrative corruption, employment justice is also established in the government departments of the province. 2- The content of all employment tests and interviews should include all the job requirements and content, as well as the evaluation of the entrepreneurial characteristics of the applicants, so that the predictive and concurrent validity of the measurement tools have the appropriate desirability so as to have the necessary capabilities to screen the applicants according to the entrepreneurial requirements at the level of government organizations of Sistan and Baluchistan province.